2017
DOI: 10.1159/000481258
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Pathological Assessment of hnRNPA1, hnRNPA2/B1, and hnRNPA3 in Familial and Sporadic Amyotrophic Lateral Sclerosis

Abstract: Background: Mutations in the genes encoding the heterogeneous nuclear ribonucleoproteins hnRNPA1 and hnRNPA2/B1 have been reported in a multisystem proteinopathy that includes amyotrophic lateral sclerosis (ALS) and inclusion body myopathy associated with Paget disease of the bone and frontotemporal dementia. Mutations were also described in the prion-like domain of hnRNPA1 in patients with classic ALS. Another hnRNP protein, hnRNPA3, has been found to be associated with the ALS/frontotemporal dementia protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…We previously identified the heterogeneous ribonucleoprotein (hnRNP) A3 as an interactor of the sense repeat RNA. We and others also found that hnRNPA3 is mislocalized from the nucleus to the cytoplasm specifically in hippocampal, cerebellar, and spinal motor neurons of C9orf72 patients [17,41]. Moreover, mislocalized hnRNPA3 colocalizes with poly-glycine-alanine (poly-GA) deposits [42].…”
Section: Introductionmentioning
confidence: 56%
“…We previously identified the heterogeneous ribonucleoprotein (hnRNP) A3 as an interactor of the sense repeat RNA. We and others also found that hnRNPA3 is mislocalized from the nucleus to the cytoplasm specifically in hippocampal, cerebellar, and spinal motor neurons of C9orf72 patients [17,41]. Moreover, mislocalized hnRNPA3 colocalizes with poly-glycine-alanine (poly-GA) deposits [42].…”
Section: Introductionmentioning
confidence: 56%
“…First, hnRNPA3 was found to bind to mutant C9ORF72 RNA in ALS and could mediate some of its toxic effects [146,147]. Furthermore, hnRNPA3 was also reported to be present in TDP43, p62 immunoreactive dipeptide repeat (DPR) inclusions in C9orf72 cases [148,149] further linking hnRNPA3 to C9orf72 ALS/FTD. Second, mutations in hnRNPA1 and hnRNPA2B1 have been identified in multisystem proteinopathy, a disorder combining IBM, FTD, ALS or Paget's disease of the bone (PDB) [20].…”
Section: Other Hnrnpsmentioning
confidence: 99%
“…Immunohistochemistry (IHC) analysis of CHCHD10 for visualisation of staining patterns and semi-quantification of protein levels in motor cortex and frontal cortex tissues was performed on spinal cord, motor cortex and frontal cortex tissue sections as previously described using rabbit polyclonal anti-CHCHD10 (1:400; Sigma-Aldrich, Missouri, USA) 38. To assess colocalisation between CHCHD10 and phosphorylated TDP-43 or a mitochondrial marker VDAC1, dual immunofluorescence (IF) was performed on spinal cord, motor cortex and frontal cortex tissues using primary anti-CHCHD10 and either mouse monoclonal anti-VDAC1 (1:500, BioLegend, California, USA), or mouse monoclonal anti-TDP-43 phosphorylated Ser409/410 (1:5000; Cosmo Bio, Japan) antibodies, followed by relevant Alexa Fluor conjugated secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify CHCHD10 protein expression in spinal cord tissues, the mean CHCHD10 fluorescence intensity from at least four motor neurons were obtained using methods described by Fifita et al 38. For frontal cortex tissues, the semi-quantification was performed by a researcher and each section was categorised into strong, moderate or weak based on staining level blindly.…”
Section: Methodsmentioning
confidence: 99%